Methodological strategies in environmental education. Case study of a natural science teacher from a public educational institution - Marcelo Veliz, Belmira Yunet (2022)
The research is part of the environmental approach that educational institutions must    address in the face of the urgency that exists to act and make environmental commitments for local, regional and global environmental threats. The, it is up to the teacher to apply methodological strategies in environmental training. The research will provide us with information about the actions that the teacher has been taking from his area of learning and be able to identify the strategies applied to identify and analyze an environmental problem of their environment to promote environmental awareness in students.